Effect of Ti on dibenzothiophene hydrodesulfurization performance over bulk Ni2P. (February 2019) - Han, Chunbao; Song, Hua; Jiang, Nan; Chen, Yanguang; Li, Feng; Hao, Tianzhen
A series of Ti-incorporated bulk Ni2 P catalysts was prepared by means of temperature-programmed reduction, and the role of metallic Ti on the structure and catalytic activity of the Ni2 P catalysts was studied. For this purpose, bulk Ni2 P catalysts with metal Ti contents of 0.005 wt%, 0.01 wt%, and 0.02 wt% were synthesized. X-ray diffraction, CO uptake, Brunauer–Emmett–Teller measurements, and X-ray photoelectron spectroscopy were utilized to characterize the catalysts. Addition of titanium could increase the surface area and promote the formation of small, highly dispersed Ni2 P particles. The Ti0.02 -Ni2 P system with a Ti molar fraction of 0.02 showed the highest hydrodesulfurization activity of 99.6%, which was an increase of 44% compared with that found for the bulk Ni2 P.